Cerebral Babesiosis in a Gir Bullock and its Successful Therapeutic Management - Solanki, JB; Thakre, BJ; Kumar, N; Patel, DC; Patel, YG (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Among haemoprotozoan diseases of the animals, babesiosis is a tick-transmitted disease caused by protozoans of the genus Babesia and it is characterized by haemolytic anemia and fever, with occasional hemoglobinuria and death (Ristic, 1981). Among six species causing bovine babesiosis, B. bigemina and B. bovis are the most important in tropical and subtropical regions (Radostits et al., 2008). The one host tick Boophilus microplus is responsible for transmission of the disease in India, both by trans-stadial and transovarian routes (Taylor et al., 2007; Lefevre et al., 2010). We came across an unusual and interesting observation about the Babesia associated with the cerebral form of the disease, the “cerebral babesiosis” in a Gir bullock, hence reporting in this communication.